Cement for fast-setting reinforced concrete products and preparation method thereof
By surface coating of gypsum powder, combined with flexible polymerized monomers and low boiling point substances, the problems of long solidification time and insufficient early strength in sprayed concrete construction are solved, and the rapid solidification and crack resistance of concrete are improved, reducing the The amount of quick-coagulant is used, and it improves the resistance to permeability and compressive strength.
Patent Information
- Application Number
- CN202410448725.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-15
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-04-15
AI Technical Summary
Concrete is prone to rebound and fall during sprayed concrete construction, which affects the construction quality. The existing accelerator has limited improvements to concrete and cannot effectively shorten the solidification time and improve early strength.
By surface coating of gypsum powder, using flexible polymeric monomers, flexible crosslinkers and low boiling point substances, a stable coating layer is formed, reducing the shedding of gypsum particles, shortening the solidification time of concrete, and gasifying the low boiling point substances Expansion forms holes, which promotes gypsum to participate in the curing reaction.
It achieves rapid acquisition of early strength of concrete and improves crack resistance, reduces the amount of fast-setting agent, reduces the internal microcracks of concrete, and improves the resistance to permeability and compressive strength.
Smart Images

Figure BDA0004791919380000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete preparation and modification, and particularly relates to cement used in fast-setting reinforced concrete products and a preparation method thereof. Background Art
[0002] Compared with traditional concrete construction, shotcrete is a construction method that uses a sprayer to spray pre-mixed cement, sand, gravel, water and some admixtures onto the surface of the substrate at a faster speed. This can greatly increase the construction speed and save labor. However, in this spraying construction method, concrete is more likely to rebound and fall, affecting the construction quality. In order to improve this situation and make concrete more suitable for this spraying construction method, it is necessary to shorten the setting time of concrete and increase its early strength, so that the sprayed concrete can stay on the surface of the substrate more stably and improve the construction quality.
[0003] In the prior art, the setting time of concrete is generally shortened and its early strength is improved by adding an accelerator to fresh concrete. However, except for accelerating the curing of concrete, the contribution of the accelerator to other aspects of concrete is relatively weak, and its function is relatively single. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing cement for use in fast-setting reinforced concrete products:
[0005] (1) Surface coating treatment of gypsum powder
[0006] The gypsum powder, the flexible polymerization monomer, the flexible cross-linking agent, the initiator, the low boiling point substance and the first emulsifier are fully mixed as the oil phase, the obtained oil phase is mixed with the water phase, and the polymerization is initiated under pressure to achieve stable coating of the gypsum powder.
[0007] The flexible polymerizable monomer is one or more of methyl acrylate, ethyl methacrylate, n-butyl methacrylate, and isobutyl methacrylate; the flexible crosslinking agent is trimethylolpropane triacrylate and / or trimethylolpropane trimethacrylate; the low boiling point substance is n-pentane;
[0008] The particle size of gypsum powder is 100μm~500μm.
[0009] The weight ratio of gypsum powder, flexible polymer monomer, flexible cross-linking agent, initiator, low boiling point substance and first emulsifier is 30-35:15-20:1-2:0.1-0.5:3-6:5-10.
[0010] The aqueous phase, calculated by weight, includes 100 parts by weight of water, 4 to 10 parts by weight of a dispersion stabilizer, and 2 to 4 parts by weight of a second emulsifier.
[0011] The mass ratio between the water phase and the oil phase is 100:20-30.
[0012] The polymerization initiation operation is to mix the water phase and the oil phase to obtain a dispersed system, react at 65-90°C for 10-14 hours under a pressure of 0.2-0.35 MPa, filter, and dry the filter cake to obtain a stably coated gypsum powder.
[0013] In step (1) here, the gypsum powder particles are first dispersed in the oil phase by the first emulsifier, and then mixed with the water phase to form an "oil-in-water" emulsion, which is conducive to the gypsum powder particles being dispersed as evenly as possible in each latex particle of the emulsion. The polymerization reaction occurs independently in each latex particle, which can greatly reduce the gypsum particles from being further gelled together during polymerization, and maintain the dispersibility between the gypsum particles after polymerization and coating.
[0014] In addition, the polymerization is initiated under pressure to avoid the escape of low-boiling-point substances due to the increase in temperature of the polymerization reaction;
[0015] (2) mixing the surface-coated gypsum powder obtained in step (1), silicate cement clinker and limestone to obtain cement,
[0016] The weight ratio of the surface-coated gypsum powder, silicate cement clinker and limestone obtained in step (1) is 5-10:80-90:5-10.
[0017] The present invention also provides cement prepared by the above preparation method.
[0018] The beneficial effects of the present invention are:
[0019] Although one of the components of cement, tricalcium aluminate (accounting for about 5-12% of the weight of Portland cement clinker), will quickly undergo hydration reaction and gelation when it comes into contact with water, thus giving concrete early strength during construction. However, the chemical composition of gypsum, another component of cement, which is used to promote the crack resistance, service strength and durability of concrete, is calcium sulfate dihydrate. Since calcium sulfate is stably combined with two crystal waters, it can dissolve relatively smoothly when it comes into contact with water. At the same time, it will also react with the gel formed by the hydration reaction of tricalcium aluminate to form ettringite, which will coat the surface of tricalcium aluminate gel to form a barrier to water, thereby slowing down the gelation speed of tricalcium aluminate, that is, delaying the early solidification of concrete.
[0020] In this regard, the present invention coats and crosslinks the surface of the gypsum particles in advance. The crosslinked molecular structure can make the coating layer on the surface of the gypsum more stable, thereby reducing the shedding of the coating layer during the mixing preparation and subsequent construction of the cement based on the gypsum. Similarly, since the coating material is a crosslinked hydrophobic substance, the coating material will not dissolve or separate from the gypsum particles in the early stage of adding water to the gypsum-based cement to prepare concrete, thereby fully avoiding the adverse effects of gypsum on the internal curing and crosslinking rate of the concrete in the early stage, so that the concrete can obtain early strength faster and initially cure and set, which provides favorable conditions for shotcrete and can reduce the amount of accelerator used during the shotcrete operation.
[0021] However, as the curing reaction inside the concrete continues, the reaction releases heat and gradually increases the temperature inside the concrete. Since the coating polymer is formed by the polymerization of flexible monomers, it has a low glass transition temperature and softens when heated. At the same time, the hydrophobic low-boiling point substances originally dispersed and doped inside the coating vaporize and expand greatly when heated, which takes advantage of the situation to stretch the softened coating and gradually detach from the coating, thereby gradually forming distributed holes on the coating, so that the originally coated gypsum material contacts the water in the external concrete through these holes, dissolves from the inside of the coating, and participates in the curing reaction of the concrete. Because the gypsum component itself is beneficial to the crack resistance, service strength and durability of concrete, this is also one of the original intentions of adding gypsum to cement. However, the gypsum in this scheme ultimately highlights the coating and participates in the curing reaction of cement and concrete to play a strengthening role. It can be seen that the utilization rate of gypsum is not significantly affected by the coating of gypsum in the early stage in this scheme.
[0022] On the other hand, during the hardening process, the cement concrete system will shrink locally and eventually lead to the appearance of cracks. In this solution, the low-boiling point substances in the coating layer are vaporized by the heat of curing to form bubbles in the cement, which can also alleviate the shrinkage of the cement during the curing process to a certain extent, reduce the appearance of micro cracks in the cement concrete, and help the produced concrete products to have stronger anti-permeability.
[0023] It can be seen that in this scheme, the low-boiling point substance in the coating layer is vaporized and expanded due to the heat of reaction, thereby achieving the effects of releasing gypsum and alleviating cement shrinkage at the same time. DETAILED DESCRIPTION
[0024] Example 1
[0025] (1) Surface coating treatment of gypsum powder
[0026] 32 parts by weight of gypsum powder with a particle size uniformly distributed between 400 μm and 500 μm, 15 parts by weight of isobutyl methacrylate, 1 part by weight of trimethylolpropane triacrylate, 0.2 parts by weight of benzoyl peroxide, 4 parts by weight of n-pentane, 7 parts by weight of sodium lauryl sulfate, and 30 parts by weight of ethylene glycol were mixed at room temperature (25° C., the same below) to form an oil phase.
[0027] 6 parts by weight of sodium chloride, 2 parts by weight of sodium lauryl sulfate, and 100 parts by weight of water were uniformly mixed at room temperature to form the aqueous phase.
[0028] Under normal temperature stirring, the oil phase obtained above is added dropwise to the water phase obtained above according to the mass ratio of the water phase to the oil phase of 100:30. After the addition is completed, stirring is continued for 1 hour. The obtained dispersion suspension is transferred to a high-pressure reactor, heated to 75° C. in a nitrogen atmosphere of 0.3 MPa for reaction for 12 hours, cooled to room temperature and then reduced to normal pressure, filtered, and the filter cake is naturally air-dried to obtain a stably coated gypsum powder;
[0029] (2) The surface-coated gypsum powder obtained in step (1), silicate cement clinker, limestone, and coal-fired slag are mixed in a weight ratio of 7:88:5:4 to obtain cement.
[0030] Example 2
[0031] (1) Surface coating treatment of gypsum powder
[0032] 35 parts by weight of gypsum powder with a particle size uniformly distributed between 300 μm and 400 μm, 8 parts by weight of isobutyl methacrylate, 7 parts by weight of n-butyl methacrylate, 3 parts by weight of ethyl methacrylate, 1.5 parts by weight of trimethylolpropane trimethacrylate, 0.3 parts by weight of benzoyl peroxide, 5 parts by weight of n-pentane, 8 parts by weight of sodium lauryl sulfate, and 40 parts by weight of ethylene glycol are mixed at room temperature to form an oil phase.
[0033] 7 parts by weight of sodium chloride, 2 parts by weight of sodium lauryl sulfate, and 100 parts by weight of water were uniformly mixed at room temperature to form the aqueous phase.
[0034] Under normal temperature stirring, the oil phase obtained above is added dropwise to the water phase obtained above according to the mass ratio of the water phase to the oil phase of 100:20. After the addition is completed, stirring is continued for 1 hour. The obtained dispersion suspension is transferred to a high-pressure reactor, heated to 70° C. in a nitrogen atmosphere of 0.26 MPa for 14 hours, cooled to room temperature and then reduced to normal pressure, filtered, and the filter cake is naturally air-dried to obtain a stably coated gypsum powder;
[0035] (2) The surface-coated gypsum powder obtained in step (1), silicate cement clinker, limestone, and coal-fired slag are mixed in a weight ratio of 8:85:7:4 to obtain cement.
[0036] Example 3
[0037] (1) Surface coating treatment of gypsum powder
[0038] 30 parts by weight of gypsum powder with a particle size uniformly distributed between 400 μm and 500 μm, 12 parts by weight of isobutyl methacrylate, 4 parts by weight of n-butyl methacrylate, 0.5 parts by weight of trimethylolpropane triacrylate, 0.5 parts by weight of trimethylolpropane trimethacrylate, 0.3 parts by weight of benzoyl peroxide, 3.5 parts by weight of n-pentane, 6 parts by weight of sodium lauryl sulfate, and 30 parts by weight of ethylene glycol are mixed at room temperature to form an oil phase.
[0039] 5 parts by weight of sodium chloride, 3 parts by weight of sodium lauryl sulfate and 100 parts by weight of water were uniformly mixed at room temperature to form the aqueous phase.
[0040] Under normal temperature stirring, the oil phase obtained above is added dropwise to the water phase obtained above according to the mass ratio of the water phase to the oil phase of 100:30. After the addition is completed, stirring is continued for 1 hour. The obtained dispersion suspension is transferred to a high-pressure reactor, heated to 78° C. in a nitrogen atmosphere of 0.35 MPa for 10 hours, cooled to room temperature and then reduced to normal pressure, filtered, and the filter cake is naturally air-dried to obtain a stably coated gypsum powder;
[0041] (2) The surface-coated gypsum powder obtained in step (1), silicate cement clinker, limestone, and coal-fired slag are mixed in a weight ratio of 6:88:4:2 to obtain cement.
[0042] Comparative Example 1
[0043] The gypsum powder was not subjected to surface coating treatment, and the remaining components and operations were the same as those in Example 1:
[0044] The cement is obtained by mixing gypsum powder with particle sizes uniformly distributed between 400 μm and 500 μm, silicate cement clinker, limestone and coal slag in a weight ratio of 4.3:88:5:4.
[0045] Comparative Example 2
[0046] When the gypsum powder is subjected to surface coating treatment, no low-boiling-point substance is added to the coating layer, and the remaining components and operations are the same as those in Example 1:
[0047] (1) Surface coating treatment of gypsum powder
[0048] 32 parts by weight of gypsum powder with a particle size uniformly distributed between 400 μm and 500 μm, 15 parts by weight of isobutyl methacrylate, 1 part by weight of trimethylolpropane triacrylate, 0.2 parts by weight of benzoyl peroxide, 7 parts by weight of sodium lauryl sulfate, and 30 parts by weight of ethylene glycol are mixed at room temperature to form an oil phase.
[0049] 6 parts by weight of sodium chloride, 2 parts by weight of sodium lauryl sulfate, and 100 parts by weight of water were uniformly mixed at room temperature to form the aqueous phase.
[0050] Under normal temperature stirring, the oil phase obtained above is added dropwise to the water phase obtained above according to the mass ratio of the water phase to the oil phase of 100:30. After the addition is completed, stirring is continued for 1 hour. The obtained dispersion suspension is transferred to a high-pressure reactor, heated to 75° C. in a nitrogen atmosphere of 0.3 MPa for reaction for 12 hours, cooled to room temperature and then reduced to normal pressure, filtered, and the filter cake is naturally air-dried to obtain a stably coated gypsum powder;
[0051] (2) The surface-coated gypsum powder obtained in step (1), silicate cement clinker, limestone, and coal-fired slag are mixed in a weight ratio of 7:88:5:4 to obtain cement.
[0052] Comparative Example 3
[0053] The coating material and gypsum powder are added to the cement separately, and the other components and operations are the same as those in Example 1:
[0054] (1) 15 parts by weight of isobutyl methacrylate, 1 part by weight of trimethylolpropane triacrylate, 0.2 parts by weight of benzoyl peroxide, 4 parts by weight of n-pentane, 7 parts by weight of sodium lauryl sulfate, and 30 parts by weight of ethylene glycol were mixed at room temperature to form an oil phase.
[0055] 6 parts by weight of sodium chloride, 2 parts by weight of sodium lauryl sulfate, and 100 parts by weight of water were uniformly mixed at room temperature to form the aqueous phase.
[0056] Under normal temperature stirring, the oil phase obtained above is added dropwise to the water phase obtained above according to the mass ratio of the water phase to the oil phase of 100:19. After the addition is completed, stirring is continued for 1 hour. The obtained dispersion suspension is transferred to a high-pressure reactor, heated to 75° C. in a nitrogen atmosphere of 0.3 MPa for reaction for 12 hours, cooled to room temperature and then reduced to normal pressure, filtered, and the filter cake is naturally air-dried to obtain polymer microspheres.
[0057] (2) The polymer microspheres obtained in step (1), gypsum powder with a particle size uniformly distributed between 400 μm and 500 μm, silicate cement clinker, limestone, and coal slag are mixed in a weight ratio of 2.7:4.3:88:5:4 to obtain cement.
[0058] The cement prepared in the above-mentioned embodiments and comparative embodiments was tested and the results are shown in Table 1:
[0059] Table 1
[0060]
[0061] Considering that the cement in this scheme may solidify faster after mixing with water, the "initial setting time" and "final setting time" in Table 1 are measured with reference to the standard JC477-2005 "Accelerator for Shotcrete", and the measurement operation is as follows:
[0062] In an indoor test environment at 20°C, weigh 400g of cement and place it in a mixing pot. Add 160mL of water to it at one time, stir it quickly for 30s, and then put the mixed material into a round mold. After manual vibration for several times (sufficient), cut off the excess cement slurry and smooth the surface with a clean scraper (the above operation time should not exceed 50s from the time of adding water). Then put the round mold filled with cement slurry under the cement slurry standard consistency and setting time measuring instrument. After the tip of the test needle contacts the surface of the cement slurry, quickly loosen the fixing screw on the measuring instrument rod, and the test needle is freely inserted into the cement slurry. Observe the pointer reading and measure it every 10s until the final setting. Among them, when the test needle sinks into the cement slurry and the distance from the bottom plate is 4mm±1mm, it is considered to have reached the initial setting, and the initial setting time (calculated from the time of adding water) is recorded; when the sinking depth of the test needle into the cement slurry is less than 0.5mm, it is considered to have reached the final setting, and the final setting time (calculated from the time of adding water) is recorded. Each sample was tested twice and the test results were averaged.
[0063] The "1d compressive strength" and "28d compressive strength" in Table 1 are also measured with reference to the standard JC477-2005 "Accelerator for Shotcrete", and the measurement operation is as follows:
[0064] According to the mass ratio of cement to sand of 1:1.5 and the water-cement ratio of 0.5, 900g of cement and 1350g of standard sand were weighed in a test environment at 20℃, and 450mL of water was added to the mixture after mixing evenly. After stirring for 50s, the mixture was immediately put into a test mold of 40mm×40mm×160mm, and immediately vibrated on a mortar vibration table for 30s (sufficiently), then the excess was scraped off and smoothed. According to the above operation, two groups of test blocks were made for each cement, with three blocks in each group. One group of test blocks was placed in a room at 20℃, and the 1d compressive strength was measured immediately after demoulding after 24 hours (calculated from the time of water addition) (the result was the average of the three test blocks in this group); the other group of test blocks was placed in a standard curing room at 20℃ and 95% humidity for curing, and the 28d compressive strength was measured immediately after demoulding after 28d (calculated from the time of water addition) (the result was the average of the three test blocks in this group).
[0065] The "impermeability" in Table 1 is measured with reference to GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", and the measurement operation is as follows:
[0066] According to the mass ratio of cement to sand of 1:1.5 and the water-cement ratio of 0.5, in a test environment at 20°C, weigh 900g of cement and 1350g of standard sand, mix them evenly, add 450mL of water, stir them rapidly for 50s, inject the mixed material into a mold, vibrate it on a mortar vibration table for 30s, scrape off the excess part and smooth it. According to the above operation, 6 test blocks of each cement are made, and the 6 test blocks are placed in a room at 20°C. After 24 hours (starting from the time of adding water), the test blocks are demoulded, and the cement slurry film on both ends of the test blocks is brushed off with a wire brush. After the demoulded test blocks are placed in a standard curing room at 20°C and 95% humidity for 28 days, the test blocks are taken out of the curing room, wiped clean and dried until the surface of the test blocks is dry, and then a layer of melted paraffin is coated on the side of the test block as a sealing material, and the test block is pressed into a preheated test mold with an upper inner diameter of 175mm, a lower inner diameter of 185mm, and a height of 150mm by a screw presser so that the test block is flush with the bottom of the test mold (the preheating degree of the test mold is that the paraffin can slowly melt after contacting the test mold, but does not flow).
[0067] Install the above 6 test blocks of the same cement on the impermeability tester at the same time, open the valve and continuously apply water pressure to each test block. The water pressure starts from the initial 0.1MPa and increases by 0.1MPa every 8 hours, and observe the water seepage of each test block at any time. When three of the 6 test blocks of the same cement show water seepage, stop the experiment and record the water pressure at this time. The value after subtracting 0.1MPa from this value is the impermeability pressure of this cement.
[0068] Comparative Example 1 in Table 1 is equivalent to a blank control. Due to the influence of gypsum, cement solidifies and hardens at a normal speed after adding water;
[0069] Similar to Comparative Example 1 is Comparative Example 3, in which the coating material and the gypsum powder are added to the cement separately, that is, the gypsum powder is also not coated, thus affecting the setting rate of the cement at the beginning;
[0070] In Examples 1 to 3 of the present scheme, gypsum is coated in advance to avoid the interference of gypsum on the initial solidification behavior of cement. Therefore, compared with Comparative Examples 1 and 3, the solidification time is significantly shortened, thereby providing favorable conditions for shotcrete and reducing the amount of accelerator used during shotcrete operation.
[0071] On the other hand, as the solidification reaction continues to release heat, the coating on the surface of the gypsum particles in this scheme is softened by the heat, and the low-boiling point substances mixed in it vaporize and expand to form holes in the coating. The internal gypsum is dissolved and released again, and finally participates in the curing and cross-linking reaction of the cement. Therefore, the compressive strength and crack resistance of the concrete products have met expectations.
[0072] The above-mentioned "meeting expectations" is mainly obtained by comparing Example 1 of this scheme with Comparative Example 3: because the coating layer of this scheme encounters the heat release of cement curing, the low-boiling point substance therein gasifies and expands, which will eventually form some small bubbles inside the product, and Comparative Example 3 also adds a coating material mixed with low-boiling point substances, and the above-mentioned small bubble phenomenon will also occur, so it can be considered that both belong to foamed concrete (while Comparative Example 1 and Comparative Example 2 do not belong to the category of foaming and are not comparable in strength). On this basis, the gypsum of Comparative Example 3 is added to cement without any coating, and should be able to achieve the conventional utilization rate, and the compression resistance and impermeability of the product of this scheme also basically reach the level of Comparative Example 3 or even exceed it, so it can be considered that the gypsum in this scheme is ultimately basically involved in cement curing and is fully utilized.
[0073] In addition, the present solution also has improved impermeability compared to Example 1 (i.e., in the water seepage detection experiment, the cement product has a stronger ability to withstand water pressure). This is because the low-boiling point substance in the present solution vaporizes and expands in the cement after being heated to form bubbles, thereby alleviating the shrinkage of the cement during the hardening process, thereby reducing microcracks in the cement concrete.
[0074] In Comparative Example 2, although the gypsum is also coated to shorten the early setting time, since no low-boiling point substance is added to the coating layer, the coating layer cannot expand and distribute to form pores when subjected to the curing heat, so the gypsum inside the coating layer is never effectively dissolved and released, and this part of the gypsum is never utilized to participate in the curing reaction of the cement, which also leads to the low strength of the final product; at the same time, there is no gasification and expansion of low-boiling point substances in the cement, and without the intervention of gypsum, the degree of microcracks inside the product increases, and the impermeability is further reduced.
Claims
1. A method for preparing cement for use in fast-setting reinforced concrete products, characterized in that: The preparation method is as follows: (1) Surface coating treatment of gypsum powder The gypsum powder, the flexible polymer monomer, the flexible cross-linking agent, the initiator, the low boiling point substance and the first emulsifier are mixed fully as an oil phase, the obtained oil phase is mixed with the water phase, and polymerization is initiated under pressure to achieve stable coating of the gypsum powder, wherein the flexible polymer monomer is one or more of methyl acrylate, ethyl methacrylate, n-butyl methacrylate and isobutyl methacrylate, the flexible cross-linking agent is trimethylolpropane triacrylate and / or trimethylolpropane trimethacrylate, the low boiling point substance is n-pentane, and the weight ratio of the gypsum powder, the flexible polymer monomer, the flexible cross-linking agent, the initiator, the low boiling point substance and the first emulsifier is 30-35:15-20:1-2:0.1-0.5:3-6:5-10; (2) Mixing the surface-coated gypsum powder obtained in step (1), silicate cement clinker and limestone to obtain cement.
2. The method for preparing cement for rapid setting reinforced concrete products according to claim 1, characterized in that: In step (1), the particle size of the gypsum powder is 100 μm to 500 μm.
3. The method for preparing cement for rapid setting reinforced concrete products according to claim 1, characterized in that: In step (1), the aqueous phase, calculated by weight, includes 100 parts by weight of water, 4 to 10 parts by weight of a dispersion stabilizer, and 2 to 4 parts by weight of a second emulsifier.
4. The method for preparing cement for rapid setting reinforced concrete products according to claim 1, characterized in that: The mass ratio of the water phase to the oil phase is 100:20-30.
5. The method for preparing cement for rapid setting reinforced concrete products according to claim 1, characterized in that: In step (2), the weight ratio of the surface-coated gypsum powder, the silicate cement clinker and the limestone obtained in step (1) is 5-10:80-90:5-10.
6. Cement prepared by the method for preparing cement for rapid-setting reinforced concrete products according to any one of claims 1 to 5.
